Head injuries in youth soccer players presenting to the emergency department. Issue 4 (25th March 2005) - Pickett, W; Streight, S; Simpson, K; Brison, R J
Abstract : Background: There has been recent concern about neuropsychological injuries experienced by soccer players, particularly related to the purposeful heading of the ball. There are few population based analyses examining whether this is a legitimate concern. Objectives: To explore, using an existing injury surveillance system, one of many parts of this issue: acute injuries requiring emergency medical care experienced by youth soccer players. Methods: Descriptive epidemiological analysis of emergency department injury surveillance data (1996–2001) for youths aged 10–24 years from the Kingston sites of the Canadian Hospital Injury Reporting and Prevention Program. Results: A total of 1714 cases of soccer injury were identified (mean 286 a year); 235 (13.7%) involved diagnoses of injuries to the head. Leading mechanical factors resulting in head injury were contact with other players or persons (153/235; 65.1%) and balls (62/235; 26.4%). Heading was reported in 4/62 (6%) of the ball contact injuries, and attempted heading was reported in 15/153 (9.8%) of the cases involving person to person contact. Unspecified head to head contact between players was reported in 39 cases. Conclusions: Minor head injuries that result in emergency medical treatment do not happen often in youth soccer, and very few can be attributed to the purposeful heading of the ball. Player contact injuries appear to be a more important injury control concern. This study informs one of many aspects of the soccer heading injury debate.